KAJIAN PENGELOLAAN EKOWISATA PADA TAMAN NASIONAL BANTIMURUNG BULUSARAUNG PROVINSI SULAWESI SELATAN (Study Kasus Site Pattunuang Asue) - Iqbal Abadi Rasjid; Amir Tjoneng; Iskandar Hasan (Percetakan Umi Toaha Makassar, 2018)
Site Pattunuang Asue is one of the leading ecotourism development sites located in Bantimurung Bulusaraung National Park. Trend increase in number of tourist visits from year to year on site Pattunuang Asue. This study aims to 1) identify potential ODTWA, 2) identify the carrying capacity, and 3) formulate tourism management strategy Pattunuang Asue. Analysis of the potential and natural tourist attraction refers to the Guideline for the Assessment of Analysis of Regional Operations-Object and Natural Attraction (ADO-ODTWA), Ditjen PHKA 2003. Analysis of carrying capacity using Cifuentes formula by calculating the physical carrying capacity and effective carrying capacity. SWOT analysis is used as a reference in establishing an optimal tourism management strategy on Pattunuang Asue site.There are 5 parameters of ADO-ODTWA criteria that are: natural resource attractiveness, accessibility, accommodation, facilities and infrastructure and socio-culture. Assessment of ADO-ODTWA is used to determine the feasibility index of the Pattunuang Asue site development. The result of the analysis of the effective carrying capacity of 1,368 visitors/day, the number is still below the average number of visits during the last 5 years as many as 37 visitors/day. Results of SWOT Analysis, the priority ecotourism management strategy that is developing the potential of natural resources as a tourist attraction with community involvement, developing service center and information about the potential of Pattunuang Asue tourism site, improving the accommodation facilities in Pattunuang Asue site.